Tai Chi Chuan teaching on alleviating mental fatigue among college students: insights from ERPs - Ji, Ruimin; Li, Jiayu (Frontiers in Psychology, 2025)
BackgroundMental fatigue is a prevalent issue, especially among college students, which significantly impacts learning efficiency. Existing interventions like caffeine use have side-effects, highlighting the need for alternative approaches. Tai Chi Chuan (TCC), a traditional Chinese mind -body exercise, shows promise in alleviating mental fatigue, yet its neural mechanisms on alleviating mental fatigue, particularly from the perspective of inhibitory control, remain unclear.ObjectivesThis study aimed to fill this gap by investigating the effects of TCC on mental fatigue and cognitive function in college students using ERP measures based on the Go/NoGo task.MethodsFifty-two healthy college students were randomly assigned to the TCC group (n = 18), aerobic exercise (AE) group (n = 17), or control (CON) group (n = 17). Mental fatigue was induced via the Stroop task, followed by a 20-min intervention of TCC practice, ergometer exercise, or sitting rest. Reaction time (RT), Visual Analog Scale (VAS) scores, and EEG data were collected.ResultsThe data showed that after the Stroop task, all groups exhibited signs of mental fatigue, with increased VAS scores and RTs. However, following the 20-min intervention, the TCC group demonstrated more significant improvements in VAS scores, RTs, and ERP components (such as increased NoGo-P3 and Go-P3 amplitudes, shortened Go-P3 latencies, and decreased NoGo-N2 amplitudes) compared to the AE and CON groups.ConclusionThese findings indicate that practicing TCC can effectively alleviate mental fatigue and facilitate cognitive recovery in college students after sustained cognitive tasks. This study provides new insights into the neural mechanisms of TCC’s beneficial effects on alleviating mental fatigue.